2018
DOI: 10.1038/s41467-018-03867-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of PIK3CA and PIK3R1 somatic mutations in Chinese breast cancer patients

Abstract: Deregulation of the phosphoinositide 3-kinase (PI3K) pathway contributes to the development and progression of tumors. Here, we determine that somatic mutations in PIK3CA (44%), PIK3R1 (17%), AKT3 (15%), and PTEN (12%) are prevalent and diverse in Chinese breast cancer patients, with 60 novel mutations identified. A high proportion of tumors harbors multiple mutations, especially PIK3CA plus PIK3R1 mutations (9.0%). Next, we develop a recombination-based mutation barcoding (ReMB) library for impactful mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
106
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 127 publications
(116 citation statements)
references
References 74 publications
10
106
0
Order By: Relevance
“…For example, one study from our center compared somatic mutation frequencies of Chinese breast cancer patients with those in the TCGA dataset and found that compared with Western patients, Chinese breast cancer patients have higher frequencies of PIK3R1 somatic mutation, which contribute to cancer development and drug resistance, irrespective of biological subtype. 8 In addition, Yin et al reported double-peaked time distribution of recurrence risk in Chinese breast cancer patients, which was different from the single recurrence risk peak reported by a study in a Western population. 9 These results addressed the potential genetic and clinical differences between Chinese and Western cohorts and thus highlighted the need for studies that focused on Chinese cohorts to personalize local treatment.…”
Section: Introductionmentioning
confidence: 81%
“…For example, one study from our center compared somatic mutation frequencies of Chinese breast cancer patients with those in the TCGA dataset and found that compared with Western patients, Chinese breast cancer patients have higher frequencies of PIK3R1 somatic mutation, which contribute to cancer development and drug resistance, irrespective of biological subtype. 8 In addition, Yin et al reported double-peaked time distribution of recurrence risk in Chinese breast cancer patients, which was different from the single recurrence risk peak reported by a study in a Western population. 9 These results addressed the potential genetic and clinical differences between Chinese and Western cohorts and thus highlighted the need for studies that focused on Chinese cohorts to personalize local treatment.…”
Section: Introductionmentioning
confidence: 81%
“…A great number of variants of unknown significance (VUS) identified by genome sequencing may possess important biological function or clinical significance but need to be assessed in largeā€scale assays. At present, some studies have successfully applied moderateā€ or highā€throughput phenotyping screening to annotate the functional characteristics of VUS . Given these advances, we are encouraged to screen impactful lung metastasisā€related genetic alterations in TNBC.…”
Section: Introductionmentioning
confidence: 99%
“…At present, some studies have successfully applied moderate-or high-throughput phenotyping screening to annotate the functional characteristics of VUS. [11][12][13][14][15] Given these advances, we are encouraged to screen impactful lung metastasis-related genetic alterations in TNBC.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperactivation of PI3K signaling is one of the most common events in human cancers. 5,7 Several genetically engineered mouse models with tissue-specific H1047R mutation of PIK3CA have been reported to develop adenosquamous carcinoma, adenomyoepithelioma or heterogeneous mammary tumors. E542K, E545K and H1047R are three hotspot mutations in PIK3CA, which result in constitutively active PI3K/AKT/mTOR cascade independent of upstream signaling.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Expression of p110Ī± mutants could promote the anchorage-independent proliferation in soft agar, growth factor-independent proliferation, and cell invasion of mammary epithelial cells in vitro. 5,7 Several genetically engineered mouse models with tissue-specific H1047R mutation of PIK3CA have been reported to develop adenosquamous carcinoma, adenomyoepithelioma or heterogeneous mammary tumors. 8 Mice expressing endogenous PIK3-CA H1047R through the knock-in system could also drive the tumorigenesis in mammary tissues.…”
Section: Introductionmentioning
confidence: 99%